An avatar‐based education application to improve patients' knowledge of and response to heart attack symptoms: A pragmatic randomized controlled trial protocol. (25th July 2018) - Tongpeth, Jintana; Du, Huiyun; Clark, Robyn A.
Abstract: Aim: To evaluate the effectiveness of an interactive, avatar‐based education application to improve knowledge of and response to heart attack symptoms in people who are at risk of a heart attack. Background: Poor knowledge of heart attack symptoms is recognized as a significant barrier to timely medical treatment. Numerous studies have demonstrated that technology can assist in patient education to improve knowledge and self‐care. Design: A single‐center, non‐blinded, two parallel groups, pragmatic randomized controlled trial. Methods: Seventy patients will be recruited from the coronary care unit of a public hospital. Eligible participants will be randomized to either the usual care or the intervention group (usual care plus avatar‐based heart attack education app). The primary outcome of this study is knowledge. Secondary outcomes include response to heart attack symptoms, health service use and satisfaction. Study participants will be followed up for 6 months. Discussion: This study will evaluate the avatar‐based education app as a method to deliver vital information to patients. Participants' knowledge of and response to heart attack symptoms, and their health service use, will be assessed to evaluate the intervention effectiveness. Abstract : 目标: 评估提高心脏病患者对心脏病发作症状的了解和反应的交互式虚拟化身型教育应用的有效性。 背景: 心脏病发作症状知识方面的匮乏被视为及时治疗的重要障碍。大量研究表明, 技术可以促进患者教育, 进而提高患者知识和自我管理。 设计: 单中心非盲双平行组实用型随机对照试验。 方法: 将从公立医院的冠心病监护病房招募70例患者。将符合条件的受试者随机分配到常规护理组和干预组(常规护理+虚拟化身型心脏病发作教育应用)。本研究主要希望获得相关知识, 另外希望获得包括对心脏病发作症状的反应、健康服务的使用和满意度方面的经验。对研究受试者进行为期6个月的随访。 讨论: 本研究将虚拟化身型教育应用评估为一种向患者提供重要信息的方法。同时, 评估受试者对心脏病发作症状的了解和反应, 以及其对健康服务的使用, 从而评估干预措施的有效性。